Socio-Cultural Relations with K6 Visits to Pregnant Women Gestational Age > 36 Weeks - Supiyati; Iis Hanifah; Mega Silvian Natalia (KHD Production, 2023)
Socio-cultural is a custom carried out by someone from generation to generation based on trusted habits. One of them is the social culture in carrying out pregnancy checks according to standards known as K6 visits. Visits of K6 pregnant women are contacts of pregnant women with health workers to get ANC services according to the 10T standard, and the frequency of visits is at least six times during the gestation period, namely one time in the 1st trimester, two times in the 2nd trimester, and three times in the 3rd trimester. It aims to analyze socio-cultural relations with K6 visits. This study uses a research design analyst with a cross-sectional approach. Data were taken from interviews with respondents using questionnaires and observation sheets, carried out at the KIA Polyclinic at the Klenang Kidul Health Center on June 16 - August 22, 2022, with 30 respondents using accidental sampling. Data collection includes coding, editing, and tabulating, and then the data is analyzed manually and by computer testingChi-square. Of the 30 respondents studied, most were aged 20-35 years (50%), most of them had junior high school education (43.3%), most of them did not work (60%), the decision-makers in conducting pregnancy checks were pregnant women themselves (40 %), some are Madurese (70%), the majority are Muslim (100%), some respondents have one child (46.67%). The pregnancy status is mostly multigravida (46.67%). Most respondents were social and cultural (60%) and made K6 visits (53.3%). Data analysis in this study uses Uji Chi-Square with a value of α=0.05. The calculation results obtained a p-value < 0.05, namely 0.001 < 0.05, meaning there is a socio-cultural relationship with K6 visits at the Klenang Kidul Probolinggo Health Center. It is hoped that the Klenang Kidul Probolinggo Health Center will improve pregnancy check-up services according to the standards set by the government by providing counseling on the benefits of Antenatal Care as early as possible and not be affected by the existing social culture to reduce Maternal Mortality Rates and Infant Mortality Rates.